Covered-stent implantation to treat aortic coarctation. (March 2012) - Butera, Gianfranco; Manica, João Luiz; Chessa, Massimo; Piazza, Luciane; Negura, Diana; Micheletti, Angelo; Arcidiacono, Carmelo; Carminati, Mario
Aortic coarctation comprises approximately 7% of all known congenital heart defects. Surgery and balloon angioplasty have been performed for many years but are associated with a significant incidence of recoarctation and aneurysm formation. Although bare-stent implantation decreases the incidence of recoarctation, the risk of aortic dissection or aneurysm formation is not eliminated. Described initially to treat patients with coexistent aneurysm of the aortic wall, we currently believe that covered-stent implantation for aortic coarctation should play a more important role. Our increasing experience from expanding their indication to deal with complications from previous interventions, associated defects or particular anatomical situations has led us to conclude that most of cases of aortic coarctation in adolescents and adults should be treated by the implantation of covered stents.